Herpes simplex keratitis in children. Issue 6 (June 1994) - Beigi, B; Algawi, K; Foley-Nolan, A; O'Keefe, M
Abstract : Ophthalmic findings are reported in 31 eyes of 28 children with herpes simplex keratitis. Twenty two had dendritic ulcers, and nine had geographic ulcers or disciform stromal keratitis. After resolution of keratitis, 80% (19/22) of children with dendritic ulcers achieved corrected visual acuity of 6/9 or better, 50% (11/22) had induced astigmatism, 45% (9/22) had one to five recurrences. In the group with geographic or disciform lesions, 89% (8/9) had reduced corrected vision, 78% (7/9) had induced astigmatism which was predominantly against the rule, and 87% (7/9) had one to six recurrences.